Shoebox Sam - Barrett, Mary Brigid; Morrison, Frank, 1971- (Grand Rapids, Mich. : Zonderkidz, 2011)
On Saturdays, Delia and Jesse help Shoebox Sam, who teaches them about charity and love by not only repairing shoes for paying customers, but also giving poor and homeless people the dignity--and footwear--they need.
Booklist
Kirkus Review
School Library Journal
Booklist, July 2011
Kirkus Review, June 2011
School Library Journal, August 2011
Keywords: Charity -- Juvenile fiction; Christian life -- Juvenile fiction; Homeless persons -- Juvenile fiction; Shoes -- Juvenile fiction; Charity -- Fiction; Christian life -- Fiction; Homeless persons -- Fiction; Shoes -- Fiction; Charity -- Fiction; Christian life -- Fiction; Homeless persons -- Fiction; Shoes -- Fiction; Picture books for children